Battle of two replacement names for the genus Metagonia Kolbe, 1899 (Coleoptera: Scarabaeidae: Melolonthinae) - Lacroix, Marc; Bezděk, Aleš (Zootaxa, 2009)
Kolbe (1899) established the new subgenus Metagonia to accommodate four species of African Melolonthinae in the genus Apogonia Kirby, 1819: Apogonia platypyge Kolbe, 1899; A. platypus Kolbe, 1899; A. pusilla Laporte, 1840; and A. mediocris Kolbe, 1891. However, he did not designate a type species. Moser (1918) elevated the subgenus Metagonia Kolbe to the genus rank. This genus-group name was then used regularly in taxonomic papers dealing with the genus Apogonia and its relatives (e.g., Dalla Torre 1912; Burgeon 1945; Frey 1974, 1976). In his catalogue of Old World Diplotaxini, Bezděk (2004) subsequently designated A. mediocris as the type species of the genus Metagonia Kolbe and listed ten species belonging to this genus. However, Kolbe and all subsequent authors overlooked that the genus-group name Metagonia Kolbe was already preoccupied by Metagonia Simon, 1893, which was proposed for the Brazilian pholcid spider M. bifida Simon, 1893 (see Huber 2000 for more details).